2015
DOI: 10.3341/jkos.2015.56.4.499
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results of Intacs® Ring Implantation in Keratoconus or Keratectasia

Abstract: Purpose:To report the clinical results after the implantation of intrastromal corneal ring segments (Intacs ® ) for the correction of keratoconus or keratectasia. Methods: This retrospective study was comprised of 16 eyes treated by insertion of intrastromal corneal ring and 30 eyes treated by penetrating keratoplasty (PKP) who were diagnosed with keratoconus or keratectasia. Visual acuity, refractive outcome, keratometric values were evaluated before and at 3 months, 6 months, and 12 months postoperatively. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Late-stage ectasia requires graft surgeries such as deep anterior lamellar keratoplasty or penetrating keratoplasty. Previous studies comparing ICRS implantation with deep anterior lamellar keratoplasty or penetrating keratoplasty have indicated that graft surgery is superior to ICRS implantation [1320]. However, ICRS implantation is still an effective treatment, and is regarded as an alternative to graft surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Late-stage ectasia requires graft surgeries such as deep anterior lamellar keratoplasty or penetrating keratoplasty. Previous studies comparing ICRS implantation with deep anterior lamellar keratoplasty or penetrating keratoplasty have indicated that graft surgery is superior to ICRS implantation [1320]. However, ICRS implantation is still an effective treatment, and is regarded as an alternative to graft surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who had other ocular surface diseases, surgical history or trauma history were also excluded. The data from patients with ICRS implantation only [13] and CXL only [14] were reported previously, and were included in this study for comparison with the ICRS + CXL group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation